Pelatihan Pola Dan Segmentasi Citra Bagi Dosen Kopertip Indonesia Untuk Mendukung Penelitian Multidisiplin - Mulyawan; Nana Suarna; Gildan Jaya Muhammad Ramadhan; Muhammad Alfian Nur Rahmat (CV. Multi Kreasi Media, 2024)
Pattern recognition and image segmentation are visual data analysis techniques with broad applications in various research fields. This Community Service Program aims to provide training on pattern recognition and image segmentation for lecturers of Kopertip Indonesia. This training seeks to enhance lecturers' understanding and ability to apply these techniques as tools to support multidisciplinary research. The training material includes the fundamentals of image processing, various pattern recognition methods, image segmentation algorithms, and case studies of applications in cross-disciplinary research contexts. It is hoped that this activity can encourage the improvement of quality and interdisciplinary research collaboration within Kopertip Indonesia.